Moral responsibility and ignorance - Nanni, Milo (2018)
The aim of this thesis is to defend a version of volitionism from objections concerning the epistemic condition of moral responsibility (especially of moral culpability). My view states that an agent is morally blameworthy for her action only if (a) the action is morally wrong and (b) she has performed the action against her better judgement that the action is wrong or from a state of culpable ignorance. In chapter 1 I provide reason in favour of volitionism and against attributionism to motivate further articulation of volitionism. In chapter 2 I discuss when it is appropriate to blame an agent for holding a false belief. In chapter 3 I defend the thesis that an agent is blameworthy for performing an action only if the action is objectively wrong (the Objective View). In chapter 4 I defend the thesis that whenever an agent acts from ignorance, she is culpable for the act only if she is culpable for the ignorance from which she acts (the Ignorance Thesis). In chapter 5 I defend the thesis that moral culpability always involves akrasia (the Akrasia Thesis). Finally, in chapter 6 I will conclude the defence of my version of volitionism by undermining the thesis that in order for an agent to be morally responsible for an action, it is necessary (and sufficient when the other conditions are met) that some facts she takes to be playing a role in explaining why the action is good or bad be personally available to her (The Consciousness Thesis).